Permainan Tandu Sebagai Media Pengembangan Kerjasama Sosial Emosional Anak Dalam Kegiatan Pramuka Prasiaga - Elma Candra Luqmana; Hadi Cahyono; Eky Okviana Armyati (Educatio, 2026)
Early Childhood Education (ECE) plays an essential part in supporting children’s development however, many children are still found to have difficulties cooperating, prefer solitary play, and easily experience conflicts during group activities. This condition requires engaging and contextual stimulation strategies, one of which is group play within Pramuka Prasiaga activities, such as the stretcher game that emphasizes coordination, communication, and collaboration. This study seeks to explain how the implementation of the stretcher game and its contribution to strengthening children’s social emotional cooperation. Data were collected through observations, interviews, and documentation, validated by triangulation, and analyzed through data reduction, data display, and conclusion drawing.The results indicate that the structured implementation of the stretcher game with active teacher facilitation effectively develops empathy (not crying 100%, not getting angry 85%, listening 80%, waiting for turns 50%), affiliation (helping peers 95%, cooperating 85%), conflict resolution (sharing roles 100%), and positive habits (enjoyment 100%, not mocking 100%, listening 80%). The success of the activity is supported by school policy, teacher readiness, availability of facilities, and children’s enthusiasm, while minor obstacles such as turn-taking conflicts (50%) can be addressed through teacher guidance. Thus, the stretcher game is proven to be an effective, enjoyable, and meaningful medium for social emotional learning in ECE.